Some issues related to sustainability in the smallholder rubber sector: A case study of three major rubber growing districts - Wijesuriya Wasana; Abeywardene Vidura; Dissanayake D M A P; Edirisinghe Jagath; Herath Keminda (Journal of the Rubber Research Institute of Sri Lanka, 2007)
DL
Keywords: Participatory rural appraisal; Smallholder